Enhancing Speaking Performance: The Role of Self-Regulated Learning, Self-Confidence, and Social Interaction Among English Department Students - Muhibbah Nst; Hamzah Hamzah (STAI Hubbulwathan Duri, 2025)
Speaking is a vital component of English language learning, yet students often struggle to perform effectively due to various cognitive and social factors. This study investigates the influence of self-regulated learning (SRL), self-confidence, and social interaction on the speaking performance of English Department students. A quantitative correlational design was used, involving 55 third-semester students from STAIN Mandailing Natal. Data were collected through validated questionnaires measuring SRL, self-confidence, and social interaction, as well as a speaking performance test evaluated by two independent raters using criteria such as fluency, accuracy, and coherence. Multiple regression analysis was conducted using Minitab version 22. Findings revealed that all three variables significantly influenced students’ speaking performance. SRL showed the highest relative contribution (33.07%, effective contribution 17.56%), followed by self-confidence (27.29%, effective contribution 14.49%), and social interaction (26.53%, effective contribution 14.07%). Together, these factors accounted for 53.07% of the variance in speaking performance. The results suggest that students who actively manage their learning strategies, possess higher confidence, and engage in social interaction are more likely to excel in speaking tasks. These findings align with theories from Zimmerman and Vygotsky, emphasizing the interplay of cognitive and social factors in language development. Integrating SRL strategies, confidence-building activities, and interactive learning in EFL classrooms can significantly enhance students' speaking performance. Educators are encouraged to design pedagogical approaches that address these three domains holistically.